2020
DOI: 10.1016/j.omtm.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

MTA1, a Target of Resveratrol, Promotes Epithelial-Mesenchymal Transition of Endometriosis via ZEB2

Abstract: Endometriosis is a benign disease that shares some malignant features. Epithelial-mesenchymal transition (EMT) is involved in the pathogenesis of endometriosis. Metastasis-associated protein 1 (MTA1) plays an important role in various cancers by promoting EMT, yet there are no studies on its function in endometriosis. In the present study, we found that MTA1 was highly expressed in the ectopic endometrium of endometriosis patients and that the expression of MTA1 was related to the revised American Fertility So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 48 publications
0
24
0
2
Order By: Relevance
“…Resveratrol in doses of 10, 20, and 40 μM for 1 hr did not affect cell proliferation (Taguchi et al, 2014). On the contrary, six selected papers showed that resveratrol in different experimental conditions intervenes in cell proliferation in endometriosis and five of those studies evidenced intervention in apoptosis, too (Taguchi et al, 2016), (Khazaei et al, 2020), (Kolahdouz‐Mohammadi et al, 2020), (Ricci et al, 2013), (Kong et al, 2020), (Chen et al, 2021). Twenty‐five, 50, and 100 μM of resveratrol for 24 hr reduced human endometrial epithelial cells proliferation and increased apoptosis in primary cultures (Ricci et al, 2013); the lower doses reduced proliferation, migration, and invasiveness of human cultured EcESC (Kong et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resveratrol in doses of 10, 20, and 40 μM for 1 hr did not affect cell proliferation (Taguchi et al, 2014). On the contrary, six selected papers showed that resveratrol in different experimental conditions intervenes in cell proliferation in endometriosis and five of those studies evidenced intervention in apoptosis, too (Taguchi et al, 2016), (Khazaei et al, 2020), (Kolahdouz‐Mohammadi et al, 2020), (Ricci et al, 2013), (Kong et al, 2020), (Chen et al, 2021). Twenty‐five, 50, and 100 μM of resveratrol for 24 hr reduced human endometrial epithelial cells proliferation and increased apoptosis in primary cultures (Ricci et al, 2013); the lower doses reduced proliferation, migration, and invasiveness of human cultured EcESC (Kong et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, six selected papers showed that resveratrol in different experimental conditions intervenes in cell proliferation in endometriosis and five of those studies evidenced intervention in apoptosis, too (Taguchi et al, 2016), (Khazaei et al, 2020), (Kolahdouz‐Mohammadi et al, 2020), (Ricci et al, 2013), (Kong et al, 2020), (Chen et al, 2021). Twenty‐five, 50, and 100 μM of resveratrol for 24 hr reduced human endometrial epithelial cells proliferation and increased apoptosis in primary cultures (Ricci et al, 2013); the lower doses reduced proliferation, migration, and invasiveness of human cultured EcESC (Kong et al, 2020). As well, resveratrol (10–30 μM for 24 hr) induced a dose‐dependent reduction of invasiveness by up to 78% in cultured human ESC, (Bruner‐Tran et al, 2011) and at 25 and 50 μM suppresses epithelial–mesenchymal transition (EMT), confirmed by the decreased vimentin expression (a mesenchymal cells marker) and increased E‐cadherin expression (epithelial marker), through inhibition of expression of metastasis‐associated protein 1 (MTA1) and of Zinc Finger E‐Box Binding Homeobox 2 (ZEB2) (Kong et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kong’s team observed that resveratrol suppressed the epithelial-mesenchymal transition process in endometriosis mice and endometrial cells. In these experimental models, resveratrol downregulated the expression of metastasis-associated protein 1 (MTA1) and transcription factor zinc finger E-box-binding homeobox 2 (ZEB2), essential components that contribute to metastasis by promoting the transformation of epithelial cells into mesenchymal cells [ 126 ].…”
Section: Potential Of Polyphenol Compounds In Endometriosis Managementmentioning
confidence: 99%
“…In primary culture of eutopic endometrial epithelial cell cultures isolated from women at the proliferative phase, both resveratrol (25-100 µmol/L) and EGCG (20-100 µmol/L) significantly reduced the cell proliferation and increased the cell apoptosis. In a mouse autotransplant model, continual peritoneal injection of resveratrol (10 and 25 mg/kg/day) or EGCG (20 and 100 mg/kg/day), started at 2-week post-surgery and lasted for 4 weeks, was able to reduce the number and volume of endometriotic lesions, cell proliferation and vascular density, but to increase cell apoptosis, within the lesions; Kong et al reported that in a mouse autotransplant model, daily peritoneal injection of 25 mg/kg for 4 weeks inhibited the expression of metastasis-associated protein 1 [70], a gene product known to promote endometrial stromal cell proliferation, migration, and invasion by inducing the epithelial-mesenchymal transition. Thus, studies in mouse models uniformly demonstrated a beneficial effect of resveratrol in endometriosis-like lesions.…”
Section: Findings From Rodent Study Modelsmentioning
confidence: 99%